2013
DOI: 10.1177/1060028013503121
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sedation and Neuromuscular Blockers in Critically Ill Adults Receiving High-Frequency Oscillatory Ventilation

Abstract: High analgo-sedation doses were associated with APACHE II scores, worsening gas exchange, and NMB use. Two thirds of patients received NMBs; use was highest on day 1 and subsequently declined. The percentage of patients who received NMB during HFOV in our study was lower than that previously reported. Future research should evaluate patient outcomes with and without use of NMBs, as well as the potential to manage patients with less sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Factors that were found to be associated with NMBA use are mainly related to disease severity, as assessed by a high APACHE III score, a large alveolar–arterial oxygen gradient, and a high plateau pressure [ 2 ]. Moreover, the use of prone positioning [ 3 ], permissive hypercapnia to ensure protective ventilation, extra-corporeal membrane oxygenation (ECMO) [ 4 ] or high-frequency oscillatory ventilation may require the use of NMBAs [ 5 ]. The purpose of this narrative review is to present an updated discussion on the role of muscle paralysis during mechanical ventilation in ARDS patients, based both on pathophysiological concepts and data obtained from clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that were found to be associated with NMBA use are mainly related to disease severity, as assessed by a high APACHE III score, a large alveolar–arterial oxygen gradient, and a high plateau pressure [ 2 ]. Moreover, the use of prone positioning [ 3 ], permissive hypercapnia to ensure protective ventilation, extra-corporeal membrane oxygenation (ECMO) [ 4 ] or high-frequency oscillatory ventilation may require the use of NMBAs [ 5 ]. The purpose of this narrative review is to present an updated discussion on the role of muscle paralysis during mechanical ventilation in ARDS patients, based both on pathophysiological concepts and data obtained from clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the infant population, this is also due to unfortunate conditions in which there is meconium aspiration or pulmonary interstitial emphysema [7, 8, 24, 31]. All patients who have VILI or are at risk of developing VILI or ARDS, would be suitable candidates for HFOV [1, 3–5, 7, 8, 13, 14, 18, 22, 26, 27, 37, 38]. Variations may be necessary based on clinical disease state and patient population.…”
Section: Introductionmentioning
confidence: 99%
“…This method uses permissive hypercapnia to provide ventilatory support and maintain normal cellular function, allowing PaCO 2 to rise while maintaining an arterial pH between 7.25 and 7.30. This strategy minimizes VILI, reduces the incidence of secondary chronic lung disease, improves ventilation/perfusion (V/Q) mismatch, does not impair cardiac output, and improves lung recruitment without overdistension [1, 4, 5, 9, 11, 13, 17, 18, 25, 26, 30, 31, 34, 40, 42].…”
Section: Introductionmentioning
confidence: 99%
“…However, other work over the past 12 years has indicated that use of NMBAs in acute respiratory distress syndrome (ARDS) has been shown to improve oxygenation and decrease mortality in most hypoxemic patients [40]. What is applicable in ARDS is also applicable in ECMO because ECMO is just a further device extension beyond ventilators and high-frequency oscillators [41,42].…”
Section: Neuromuscular Blockade and Ecmo/ardsmentioning
confidence: 99%